Conditional Fgfr1 Deletion in GnRH Neurons Leads to Minor Disruptions in the Reproductive Axis of Male and Female Mice - Dela Cruz, Cynthia; Horton, Cassandra A.; Sanders, Kelsey N.; Andersen, Nathan D.; Tsai, Pei-San (Frontiers in Endocrinology, 2021)
In humans and mice, inactivating mutations in fibroblast growth factor receptor 1 (Fgfr1) lead to gonadotropin-releasing hormone (GnRH) deficiency and a host of downstream reproductive disorders. It was unclear if Fgfr1 signaling directly upon GnRH neurons critically drove the establishment of a functional GnRH system. To answer this question, we generated a mouse model with a conditional deletion of Fgfr1 in GnRH neurons using the Cre/loxP approach. These mice, called Fgfr1cKO mice, were examined along with control mice for their pubertal onset and a host of reproductive axis functions. Our results showed that Fgfr1cKO mice harbored no detectable defects in the GnRH system and pubertal onset, suffered only subtle changes in the pituitary function, but exhibited significantly disrupted testicular and ovarian morphology at 25 days of age, indicating impaired gametogenesis at a young age. However, these disruptions were transient and became undetectable in older mice. Our results suggest that Fgfr1 signaling directly on GnRH neurons supports, to some extent, the reproductive axis function in the period leading to the early phase of puberty, but is not critically required for pubertal onset or reproductive maintenance in sexually mature animals.